A Study of Littoral Foraminiferal Fauna of the Sediments Off the Lagos Coast, Southwestern Nigeria - Olayiwola, Moshood Adegboyega (2015)
This study is aimed at documenting, determining the distribution, composition, and diversity pattern, and defining the biotopes and biofacies of foraminiferal fauna with the view to characterizing the littoral environments off the Lagos Coast, Southwestern Nigeria.